Maqāṣid al-Sharīʿah as a Governance Framework: Institutionalizing Child Protection in Pontianak - Marluwi Marluwi; Baihaqi Baihaqi; Ahmad Musadad; Umi Indasyah Zahro; Tri Pujiati (Universitas Muhammadiyah Bandung, 2025)
The high rate of violence against children in Pontianak City shows that the issue of child protection is not only normative in regulations, but has become a complex social problem. This study aims to analyze the dynamics of children's involvement as victims of crime in Pontianak City and examine the governance of child protection through the perspective of maqāṣid al-syarī'ah. The research method used is qualitative with a socio-legal approach to examine the relationship between positive legal norms and the implementation of child protection at the regional level. The results of the study show that family vulnerability, weak parental supervision, unconducive social environment, and low digital literacy are the main causes of the increased risk of children becoming victims of crime. Field findings also show that the Pontianak City Regional Child Protection Commission has implemented protection governance through integrated assessment SOPs, legal and health assistance, education sustainability supervision, direct and digital complaint services, and preventive programs based on community participation. The analysis based on maqāṣid al-syarī'ah emphasizes the need to reconstruct the fiqh of child protection based on the principles of ḥifẓ al-nafs, ḥifẓ al-'aql, and ḥifẓ al-nasl as a normative foundation in child protection policies. This study recommends a stronger integration between regional regulations, institutional capacity strengthening, and internalization of the values of maqāṣid al-syarī'ah so that the child protection system in Pontianak City becomes more substantive, responsive, and holistically oriented towards the benefit of children.